THE ROLE OF INVESTMENT OPPORTUNITY SET IN MODERATING THE RELATIONSHIP BETWEEN CAPITAL STRUCTURE AND INFORMATION ASYMMETRY WITH PROFIT QUALITY - Nita Oktaviani Ginting; Nofryanti; Iin Rosini (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to analyze the role of investment opportunity set in moderating the relationship between capital structure and information asymmetry with profit quality in consumer non-cyclicals companies in Indonesia during the period 2021-2023. The study uses a sample of 96 consumer non-cyclical companies listed on the Indonesia Stock Exchange from 2021 to 2023. This study employs secondary data obtained from financial reports, annual reports published on the IDX, and historical data of the highest, lowest, and closing stock prices listed on yahoo.finance. Hypothesis testing is carried out using a panel data linear regression model with EViews 12 software. The results of this study indicate that capital structure affects profit quality, information asymmetry does not affect profit quality, investment opportunity set cannot moderate the relationship between capital structure and profit quality, and investment opportunity set cannot moderate the relationship between information asymmetry and profit quality.